(Invited)Laser Annealing in CMOS Manufacturing. (9th April 2018) - Gluschenkov, Oleg; Jagannathan, Hemanth
Abstract : Laser Annealing was introduced into mainstream CMOS manufacturing nearly a decade ago and since then has been evolving capturing new applications and expanding into new process regimes. This invited paper provides an overview of the adoption and the applications of millisecond-scale laser annealing in CMOS technologies. Building on the presented historical perspective, this paper then discusses and compares applications of nanosecond-scale laser annealing in future CMOS technologies. Mitigation of thermal pattern effects are also discussed in the context of different device architectures built on both bulk and SOI substrates.